Analysis Of The Influence Of Tomasiwa Village Unit Cooperative (KUD) On Member Welfare (A Case Study In Morela Village, Leihitu District, Central Maluku Regency, Maluku Province) - Aksel R Rahanserang; Leunard O Kakisina; Raihana Kaplale (Cita konsultindo, 2023)
How does the Tomasiwa Morella Village Unit Cooperative influence welfare members in Morella Village, Leihitu District, Central Maluku Regency, For determine the influence of the Tomasiwa Morella Village Unit Cooperative on welfare members in Morella Village, Leihitu District, Central Maluku Cooperative Regency, in improving its performance and competitiveness to provide benefits formembers and the public.. The questionnaire consists of two parts, namely the first part regarding the respondent profile and the second part regarding the research variables, namely the influence of cooperatives on the welfare of cooperative members. Influence variable cooperatives are measured through several indicators, such as management participation, supervision, training and counseling on member welfare variables. Data obtained from questionnaires and secondary data were analyzed using using multiple linear regression analysis techniques. Based on the analysis results multiple linear regression, management participation, supervision and training have major influence on member welfare. The results of data analysis show Tomasiwa Morella's village unit cooperative (KUD) business activities have a significant influence to the welfare of members. Except for the training of related members in the field of member cadre formation so that in the future they can become leaders in the KUD This is because the cooperative leader will only inherit 1 from the cooperative owner.The Influence of Tomasiwa Morella KUD on Member Welfare: This research identified that the Tomasiwa Morella Village Unit Cooperative (KUD) has positive influence on the welfare of its members. Management participation, supervision, and training contribute significantly to improvement member welfare